Constructtion of Student Well-being Scale for 4-6th Graders - Irine Kurniastuti; Saifuddin Azwar (Faculty of Psychology, Universitas Gadjah Mada, 2014)
Student well-being in the context of an elementary school in Indonesia has not been much studied. Accordingly, the effort of developing relevant indicators for revealing student well-being has not been done too. Along with the increase of public awareness of student well-being at school, appropriate tools to measure it is greatly needed. This study aimed to develop an instrument for measuring student well-being in elementary school. The scale was based on the review of research on children's well-being by Pollard and Lee and was adapted for school context using the psychological well-being approach suggested by RyffandKeyes. This study had three parallel scales, each of which was tested, on 200 respondents. Accordingly, the study involved 600respondents. The results of the analysis of the scales were used as basist for preparing a compilation scale. It was then tested on215respondents. The results of the analysis showed that 39items composed had satisfying psychometric properties, i.e. the reliability coefficient, item discrimination index, and content validity. However, the structural factor still needed to be improved.